Superior strength-ductility in laser aided additive manufactured high-strength steel by combination of intrinsic tempering and heat treatment. Issue 4 (4th July 2021) - Tan, Chaolin; Chew, Youxiang; Weng, Fei; Sui, Shang; Du, Zhenglin; Ng, Fern Lan; Bi, Guijun
ABSTRACT: This work investigated laser aided additive manufacturing (LAAM) high-strength steel by leveraging the intrinsic tempering effect to facilitate the formation of high-fraction of metal carbides (e.g. M23 C6 and M7 C3 ) in the as-built samples. The intrinsic tempering effect contributes to a superior mechanical property than traditional manufacturing methods in as-built condition, promoting subsequent heat treatments (HTs) for excellent mechanical properties. The influence of HTs on the microstructures and mechanical properties were characterised in multi-scales. A large number of carbides are intrinsically formed due to the tempering effect during deposition. The high-density dislocations in the as-built sample facilitate the formation of massive nano-twins and carbides during HT. The HTed sample achieves a true tensile stress of about 1.81 GPa together with a true strain of about 21%, achieving an excellent strength-ductility combination compared to wide-range high-strength steels processed by additive manufacturing and conventional methods. The grain and twin boundaries strengthening, precipitation strengthening and dislocation strengthening contribute to the high strength, while the good ductility originates from twinning induced plasticity (TWIP) and transformation-induced plasticity (TRIP) effects, and high work-hardening rate, during deformation. The findings imply a potential way to develop AM-customised materials by fully understanding and utilising the IHT effect.